Thematic groups characteristic for riddles - Abduvaxobova , Maxina; Akhadullayeva , Marjona (The Lingua Spectrum, 2025)
This article explores the diverse thematic landscape of riddles, categorizing them into distinct groups based on their subjects. It examines common themes such as nature (animals, plants, weather phenomena), everyday objects, human characteristics (physical traits, emotions, actions), occupations, and abstract concepts (time, truth, luck). The analysis may also consider how these thematic groups reflect cultural values and beliefs, as well as the cognitive processes involved in both creating and solving riddles. Finally, the article may discuss the educational and entertainment value of riddles across different age groups and cultures, highlighting their role in developing language skills, critical thinking, and cultural understanding. This article offers a comprehensive analysis of English and Russian riddles through thematic, structural, semantic, and cultural lenses. It categorizes riddles into thematic groups, including natural phenomena, human traits, occupations, abstract concepts, and everyday objects, highlighting how these themes mirror the cultural and social realities of their respective societies. The study investigates the structural forms of riddles – ranging from simple and complex sentences to full texts – and identifies common stylistic devices such as metaphor, personification, inversion, and homonymy. Drawing on folklore studies and cognitive linguistics, the article examines how riddles serve not only as entertainment but also as educational tools that foster memory, creativity, and critical thinking. The comparative approach reveals cross-cultural similarities and distinctions, emphasizing the riddle’s role as a reflection of collective consciousness and cultural heritage. By analyzing riddles in both folk and modern contexts, the article contributes to the understanding of how language, cognition, and culture interact in verbal art forms.